Relationship between Side Effects of Anti-tuberculosis Drugs (ATDs) and Adherence to Medication in Elderly Patients with Tuberculosis - Joko Sapto Pramono; Riana Sudding; Tini Tini (Poltekkes Kemenkes Palu, 2023)
One of the obstacles to the treatment of tuberculosis (TB) patients is the sideeffects of anti-tuberculosis drugs (ATDs) which cause patients to be reluctant to continue the medication. The elderly experience various physical and physiological changes in the bodysystem, including susceptibility to drug side effects, decreased knowledge and memory,resulting in non-compliance with taking the medication. This study aims to determine therelationship between ATDs side effects and compliance with taking medication for elderlypatients at the Tanjung Selor Health Center, Bulungan Regency, North Kalimantan Province.This study used a quantitative cross-sectional approach. The sample was taken by totalpopulation, namely elderly tuberculosis patients undergoing tuberculosis treatment as many as30 respondents. The research instrument was a questionnaire of drug side effects and ATDscompliance. Statistical test used Fisher's Exact. The results showed that most patients (76.7%)complained of OAT side effects and the rest without OAT side effects (23.3%). Treatmentcompliance was 20% compliant, and 80% were non-compliant. Fisher's Exact statistical testobtained p-value = 0.016 (< α = 0.05). It was concluded that there was a significant relationship between OAT side effects and treatment compliance in elderly patients with tuberculosis. Recommendations for health workers to give special attention to elderly patients with medication monitoring and compliance motivation. Future researchers should identify the involvement of family and health workers to monitor the side effects of anti-tuberculosis drugs.